Marketing digital y resiliencia empresarial en el sector hotelero de la provincia de Pasco-Perú - Cárdenas Sinche, José Antonio (2023)
The objective of this article was to determine whether digital marketing has a direct and significant influence on business resilience in the hotel sector in the province of Pasco. The methodology used was descriptive correlational, using the survey technique. The results were able to demonstrate the expected objective.